Faktor-faktor yang Memengaruhi Keputusan Konsumen dalam Pembelian Melon Premium di Kota Bandung (Studi Kasus pada PT. Kebun Bumi Lestari) - Immanuel, Marvel Secio; Renaldi, Eddy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The Farmhill is a premium melon producer in Indonesia whose products are spread throughout Indonesia. When compared with the price of other melons, premium melons have a higher price. However, demand, production, and marketing of this melon remain high and even increase. This does not appear to be suitable with the law of demand which states "the higher the price, the less consumer demand". This research aims to describe the characteristics of consumers and determine the factors that influence consumer decisions in purchasing premium melon. The research methods used by researchers are descriptive analysis and factor analysis. Based on the results of this research, show that nine new factors influence the decision to purchase premium melon. However, researchers only took five dominant factors, namely food safety and quality, consumer psychology, product characteristic, consumer needs, and product accessibility. The factor that has the biggest contribution is food safety and quality.